THE EFFECTS OF NEBIVOLOL AND IRBESARTAN ON CENTRAL BLOOD PRESSURE AND ARTERIAL STIFFNESS PARAMETERS IN HEMODIALYSIS PATIENTS WITH INTRADIALYTIC HYPERTENSION. (June 2018) - Bikos, A.; Loutradis, C.; Aggeloudi, E.; Karpetas, A.; Raptis, V.; Alexiadis, J.; Balaskas, I.; Liakopoulos, V.; Papagianni, A.; Sarafidis, P.A.
Abstract : Objective: Intradialytic hypertension is associated with increased cardiovascular risk. The exact mechanistic background of intradialytic hypertension is not yet fully elucidated. This study aimed to evaluate the effects of nebivolol and irbesartan in 24hour ambulatory central BP, arterial stiffness and wave reflection parameters in hemodialysis patients with intradialytic hypertension. Design and method: In a cross-over fashion 38 hemodialysis patients (age: 60.4 ± 11.1 years, male: 65.8%) with intradialytic hypertension (mean intradialytic rise >  = 10 mmHg in systolic BP (SBP) over 6 consecutive hemodialysis sessions) were randomly assigned to receive nebivolol 5 mg and subsequently irbesartan 150 mg, or vice versa. Half of the patients received a single drug-dose 1 hour before hemodialysis (n = 19) and half received the drug for a whole week before evaluation (n = 19). A two-week wash-out period took place before the initiation of the second drug. Ambulatory central BP, arterial stiffness and wave reflection parameters were estimated with the Mobil-O-Graph NG device, during a midweek dialysis-on day (24 hours). Results: In total, 20 (52.6%) patients received nebivolol first and 18 (47.4%) received irbesartan first. Weekly administration of either nebivolol or irbesartan reduced 24-hour central SBP and DBP ([Baseline: 135.50 ± 10.09/92.03 ± 9.18; Nebivolol: 126.65 ± 8.40 (p < 0.001), 87.22 ± 7.05 (p = 0.004); Irbesartan: 128.93 ± 10.76 (p = 0.058), 87.32 ± 9.34 (p = 0.056) mmHg], while nebivolol also reduced central pulse pressure (cPP) ([Baseline: 43.48 ± 12.04, Nebivolol: 39.87 ± 8.56 (p = 0.021); Irbesartan: 41.77 ± 8.22 (p = 0.377) mmHg] and pulse wave velocity (PWV) ([Baseline: 9.96 ± 2.45; Nebivolol: 9.73 ± 2.48 (p = 0.016); Irbesartan: 9.72 ± 2.72 (p = 0.073) m/s). Neither drug affected heart rate-adjusted augmentation index (AIx(75)). Patients receiving a single dose of nebivolol had significantly lower 24-hour central DBP [Baseline: 89.32 ± 12.16; Nebivolol: 85.45 ± 11.37 (p = 0.032)], but similar 24-hour central SBP, cPP, AIx(75) and PWV. No significant differences were observed in patients receiving a single dose of irbesartan. Conclusions: Weekly administration of both nebivolol and irbesartan reduce central BP and PWV, but not Aix(75). The above suggest that development of intradialytic hypertension may be primarily attributed to abnormal vasculature response to volume changes affecting both SBP and DBP.